Capillary electrophoresis for forensic drug analysis: A review - Anastos, N.; Barnett, N.; Lewis, Simon (Elsevier, 2005)
This paper reviews recent applications of capillary electrophoresis to forensic drug analysis and covers the literature since 2001. A brief overview of capillary electrophoresis is followed by a discussion of analytical applications which have been categorized into two sections: (i) drug seizures and non-biological samples, and (ii) forensic toxicology and biological samples.